2003
DOI: 10.1046/j.1468-3083.2003.00746.x
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi's sarcoma – still an enigma

Abstract: Kaposi's sarcoma (KS) is an unusual neoplasm that has proved to be an enigma in many ways since its original description in 1872. KS, a vascular tumour that is otherwise rare, is at present the most common neoplasm in patients with AIDS. The lesions contain spindle cells that share features with endothelial cells and smooth muscle cells and are in all likelihood primitive mesenchymal cells that can form vascular channels. These cells are monoclonal in origin indicating therefore that KS is a neoplasm. The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Formerly a rare tumor, the incidence of Kaposi sarcoma exploded with the onset of the AIDS epidemic, and Kaposi sarcoma is now the most common tumor seen in AIDS patients, with a disproportionate incidence among homosexual and bisexual men. [10][11][12] For this reason, an infectious etiology has long been suspected, and epidemiological, serologic, and molecular genetic studies over the past 10-15 years have identified a novel LANA expression in vascular tumors in HIV þ patients L Hammock et al herpesvirus, HHV-8, as the likely causative agent of Kaposi sarcoma. [10][11][12][13][14] HHV-8 is known to latently infect endothelial cells, as well as peripheral blood monocytes and Blymphocytes in patients with Kaposi sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Formerly a rare tumor, the incidence of Kaposi sarcoma exploded with the onset of the AIDS epidemic, and Kaposi sarcoma is now the most common tumor seen in AIDS patients, with a disproportionate incidence among homosexual and bisexual men. [10][11][12] For this reason, an infectious etiology has long been suspected, and epidemiological, serologic, and molecular genetic studies over the past 10-15 years have identified a novel LANA expression in vascular tumors in HIV þ patients L Hammock et al herpesvirus, HHV-8, as the likely causative agent of Kaposi sarcoma. [10][11][12][13][14] HHV-8 is known to latently infect endothelial cells, as well as peripheral blood monocytes and Blymphocytes in patients with Kaposi sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…The association with HHV8 infection in all forms of the disease (Babal and Pect, 2003) is consistent with a common pathologic process, but certain clinical-epidemiological aspects differentiate the course, the prognosis, and treatment of each form. Classical KS corresponds to the original description (Kaposi, 1872), and predominantly affects elderly males, with a higher incidence in southern and eastern European countries, with a predominance among Jews and people of Mediterranean descent (Ziegler et al, 1988, Mackie, 1992Franceschi and Geddes, 1995).…”
mentioning
confidence: 82%
“…First described by Moritz Kaposi [1] in 1872, Kaposi’s sarcoma (KS) is an unusual vascular neoplasm with genetic, infectious, environmental and immunological pathogenesis [2,3]. KS presents polymorphic clinical features and evolution; it generally has a relatively benign, indolent course as in the genetic-linked, classic (Mediterranean) form.…”
Section: Introductionmentioning
confidence: 99%
“…Lesions may be limited to skin or sometimes disseminate to the mucous membranes, lymph nodes or viscera [4]. Typically, the KS lesion appears as brownish-red to purple or blue-colored patches, plaques or nodules in the distal lower extremities [2]. Moreover, there are clinical morphological variants, as in AIDS patients, which commonly present as small, pink, multifocal lesions located on the upper trunk and head [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation